Transfer of the Brazilian species Calathea dorothyae to the genus Goeppertia (Marantaceae) - Braga, João Marcelo Alvarenga (Phytotaxa, 2012)
The genus Goeppertia has recently been redefined morphologically and now incorporates most species previously described as Calathea. Most species have already been transferred, but Calathea dorothyae was more recently described and is hereby transferred to Goeppertia.